Voltage Equalization Technique of Switch Series Circuit Using Clamp Circuit for High Pressure Switching - Lee, Chang-Ho; Park, Seong-Mi; Park, Sung-Jun (International Journal of Engineering and Technology, 2018)
Background/Objectives: In recent years, in order to revitalize the energy conversion paradigm for energy efficiency, researches on large capacity energy transmission using DC have been actively carried out. In the DC power transmission system, LVDC, MVDC, and HVDC are applied according to the power transmission capacity.Methods/Statistical analysis: The higher the power transmission capacity, the higher the transmission voltage becomes. Most of the DC voltage change is made by a static power converter using a semiconductor switch element. A power converter using a semiconductor switch element is difficult to increase in pressure due to the voltage strength of the semiconductor element.Findings: In this paper, we propose a new topology that can switch high voltage by using a clamp circuit to each switching device connected in series to solve the balancing problem of voltage distribution when a switching device is configured in series for high voltage switching. The validity of the proposed high - pressure switching topology is verified by applying it to the reduced - pressure converter.Improvements/Applications: The clamp circuit can limit the voltage in the transient state that occurs when the switch circuit is turned on and off, which is very helpful for stable switching operation. Therefore, this result is expected to be useful for the high voltage of DC / DC converter in the future.Â